PEMANFAATAN BAGAS SEBAGAI CAMPURAN MEDIA PERTUMBUHAN JAMUR TIRAM PUTIH - Kristianus Sunarjon Dasa; Astutik Astutik; Amir Hamzah (Universitas Tribhuwana Tunggadewi, 2011)
Growth and development of white oyster mushroom are influenced by the mushroom seeds, planting substrate, environmental conditions, and media materials. A common type of media used is sawdust mushroom growers. Bagasse is a waste of sugar production as the highest cause of pollution (35%) but contains organic matter, minerals, crude fiber, crude protein and essential nutrients needed for growing oyster mushrooms. It is therefore necessary to study with the aim to determine the effect of bagasse as the mixed media production and quality of white oyster mushrooms. The experiment was conducted at PT Endang Mushroom, Tlogomas village, Lowok waru district, Malang city started from November until April 2011. The research used Completely Randomized Design with bagasse single-dose factor i.e. without bagasse/control (P0), 10% of bagasse (P1), 20% of bagasse (P2), 30% of bagasse (P3), and 40% of bagasse (P4). The observations made on the variables: time of fruit body appears, stalk length, stalk diameter, diameter of the hood, the number and weight of the wet weight of fruit. The results concluded that the use of bagasse as the mixture of sawdust medium effected on the growth of white oyster mushrooms. The addition of 40% bagasse was capable of producing fruit bodies appear as the fastest (28 days), the largest stem diameter (2.24 cm), the largest cap diameter (8.95 cm), the highest number of fruit (37.80 fruits) and wet weight reached 444.20 grams, of fruit bodies and wet weights did not differ erent as much as 30 % of bagasse